2014
DOI: 10.1002/2014gl060591
|View full text |Cite
|
Sign up to set email alerts
|

Upper atmosphere cooling over the past 33 years

Abstract: Theoretical models and observations have suggested that the increasing greenhouse gas concentration in the troposphere causes the upper atmosphere to cool and contract. However, our understanding of the long-term trends in the upper atmosphere is still quite incomplete, due to a limited amount of available and well-calibrated data. The European Incoherent Scatter radar has gathered data in the polar ionosphere above Tromsø for over 33 years. Using this long-term data set, we have estimated the first significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 28 publications
9
47
3
Order By: Relevance
“…This gives cooling rate of ∼(3-4) K/decade analyzing a period of 30-40 years. This is close to an exospheric temperature trend of À1 to À2 K/decade estimated from satellite drag observations (Emmert, 2015) and much smaller than Tex trends inferred from ground-based ISR measurements: À18 K/ decade for noontime exospheric temperature at Millstone Hill (Oliver et al, 2014), À60 K/decade at 350 km for daytime hours at Saint Santin/Nancay (Donaldson et al, 2010), À10 to À15 K/decade at F 2 -layer heights for day-time hours at Tromso (Ogawa et al, 2014), and À20 K/decade at 350 km for daytime hours at Millstone Hill (Zhang & Holt, 2013). A recent analysis by Zhang et al (2016) of Sondrestrom and Chatanika/ Poker Flat ISR observations has shown that the high latitude long-term trend results are compared to those from the Millstone Hill mid-latitude dataset.…”
Section: Discussionsupporting
confidence: 71%
“…This gives cooling rate of ∼(3-4) K/decade analyzing a period of 30-40 years. This is close to an exospheric temperature trend of À1 to À2 K/decade estimated from satellite drag observations (Emmert, 2015) and much smaller than Tex trends inferred from ground-based ISR measurements: À18 K/ decade for noontime exospheric temperature at Millstone Hill (Oliver et al, 2014), À60 K/decade at 350 km for daytime hours at Saint Santin/Nancay (Donaldson et al, 2010), À10 to À15 K/decade at F 2 -layer heights for day-time hours at Tromso (Ogawa et al, 2014), and À20 K/decade at 350 km for daytime hours at Millstone Hill (Zhang & Holt, 2013). A recent analysis by Zhang et al (2016) of Sondrestrom and Chatanika/ Poker Flat ISR observations has shown that the high latitude long-term trend results are compared to those from the Millstone Hill mid-latitude dataset.…”
Section: Discussionsupporting
confidence: 71%
“…However, for years with higher F10.7 values the tendency of increasing fit residuals is less distinct. Ogawa et al (2014) find a non-linear relationship between upper-atmospheric temperatures and solar activity using EISCAT UHF (ultra-high frequency) radar ob- servations from 200 to 450 km altitude over Tromsø, even though it must be noted that the altitude range they look at differs from ours.…”
Section: Exploration Of Solar Flux Dependencecontrasting
confidence: 67%
“…Exospheric temperature trends estimates derived from ground‐based incoherent scatter radar (ISR) measurements have been much larger than the orbit‐derived estimates given in Table . The most recent estimates from Millstone Hill (43°N, 72°W), Saint Santin (47°N, 2°E), and Tromsø (70°N, 19°E) are, respectively, −18 K/decade [ Oliver et al ., ], −30 K/decade [ Donaldson et al ., ], and −10 to −15 K/decade [ Ogawa et al ., ]. Oliver et al .…”
Section: Resultsmentioning
confidence: 99%